Optimization of Tax Revenue in The Time of Covid-19 in Organization of Islamic Cooperation Countries (Case Studies in Egypt, Turkey, Saudi Arabia, and Pakistan) - Cindy Ayu Prasasti; Fachrounissa Zein Vitadiar; Irvan Yusuf Nugroho; Laila Masruro Pimada (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
In-state revenue, the tax sector is one of the biggest contributors to the country's infrastructure development. Tax contribution to protecting the financial sector. However, lately, the condition of some countries is less stable because of the COVID-19 virus which limits all human activities that have an impact on decreasing tax revenues and economic decline. Thus, the purpose of this study is to analyze the right policies to be implemented by the Indonesian government in optimizing tax revenues in the midst of the COVID-19 pandemic. Descriptive qualitative method is used to directly see the impact and tax regulations set by the governments of the member countries of the Islamic Cooperation Organization (OIC). By looking at the results of the research, the government's policy of providing tax breaks and cuts in Indonesia with an unstable financial condition provides an opportunity for people to make tax payments. This must also be supported by increased public awareness of the importance of taxes and regulations or tax violation fines. The government can also optimize taxes by increasing the accurate and selective supervision of goods that endanger human health so that they do not occur in other expenses caused by goods entering Indonesia.